Andalusian and Classical Ottoman Mosque Architecture Features - Coskun, Hamit; Durakoğlu, Abdullah; Altıparmak, İpek Beyza (My University, 2024)
Cultures have met and influenced each other throughout history, and new and original products have emerged. Andalusian works, which were formed under the influence of Islamic and Christian architectural culture in history, and Ottoman architectural works, which were put forward by considering aesthetics and symmetry, are worth examining and are the subject of many scientific studies. In this study, the characteristics of Andalusian and Ottoman mosque architectures, which represent two peaks in Islamic civilization, were examined and compared. There is a perfect harmony be- tween the multi-column and horseshoe-shaped arches in Andalusian mosques, but this situation creates a dim image. In terms of external appearance, it is reported that the mosques face north, and there is one square-based minaret here. The minarets, which have survived to the present day, have the appearance of a high building and terraces on the upper parts used for observation purposes. In the Ottoman Empire, minarets were built more than once in mosques built by dynasty members and in sultanate mosques, giving the city an aesthetic appearance and being symmetrical with the mosque. In this study, architectural features of mosques in terms of columns, plan, facade arrangement, light order and amount, mortar figures, plant and flower figures, tile decoration, Kufic script, use of bricks, number of minarets, the shape of minarets, arch, color type, and construction process. These features were compared and dis- cussed in the light of social and cultural effects.
Keywords: Architecture; Mosque; Culture.; Ottoman; Andalusia